2017
DOI: 10.1680/jgele.17.00081
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of biopolymer-stabilised soil-based construction materials

Abstract: Soil-based construction materials are of interest as structural building materials due to their green credentials, as well as being present in many historical structures. For effective conservation of the latter, and to motivate greater uptake for new construction, understanding of the mechanical and hydraulic properties of these materials is in need of improvement. Earthen construction materials can be considered to be manufactured unsaturated soils, and advances in understanding can be made by considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 20 publications
7
64
0
Order By: Relevance
“…Splitting tensile strength test. The increase of soil tensile strength with the addition of XG and GG was proven by direct tensile tests performed by Muguda et al 43 . They have found that the tensile strength of soil increases with biopolymer concentration and time.…”
Section: Resultsmentioning
confidence: 92%
“…Splitting tensile strength test. The increase of soil tensile strength with the addition of XG and GG was proven by direct tensile tests performed by Muguda et al 43 . They have found that the tensile strength of soil increases with biopolymer concentration and time.…”
Section: Resultsmentioning
confidence: 92%
“…Methodology Stabilisation using biopolymers is achieved through "hydrogels" which are formed through the interaction of soil, biopolymer and water particles. Unlike cementitious bonds formed due to hydration of cement, these "hydrogels" bind soil particles through a combination of chemical bonds and soil suction (Muguda, et al, 2017). As these hydrogels become susceptible to weakening on contact with water, durability tests such as accelerated erosion tests, spray tests, and wire brush tests were considered to be too vigorous and hence an alternative test was chosen, namely the "Geelong" Test (NZS 4298, 1998).…”
Section: Materials and Methods: Durability Testingmentioning
confidence: 99%
“…Recent work reported in Aguilar, et al, (2016) and Nakamatsu, et al, (2017) has investigated the use of biopolymers (namely chitosan and carrageenan) as stabilisers and has reported that the addition of these biopolymers improved mechanical and durability performance of earthen materials. Very recently, the mechanical behaviour of earthen construction materials stabilised with the biopolymers guar gum and xanthan gum was studied by Muguda, et al, (2017) which showed that the addition of these biopolymers improved compressive and tensile strengths. These biopolymers sequester CO 2 during production (Chang et al, 2016;Krishna Leela & Sharma, 2000) in contrast to cement, which leads to the opposite, however energy required in production of the gums may be much greater than for an equivalent amount of cement (e.g.…”
Section: Durability Of Earthen Construction Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Lambert and Randall [16] have shown that the green brick can be manufactured with the use of human urine as a urea source [17]. Researchers have also explored possible admixtures to strengthen the consolidated samples [18,19] . Bio-based admixtures using additives such as xanthan gum, gellan gum, welan gum lignosulfonates are being explored by researchers for improvement in durability [20].…”
Section: Introductionmentioning
confidence: 99%